GEOGRAFIYA PÁNIN OQÍTÍWDA «JOYBAR» SABAǴÍNAN PAYDALANÍWDÍŃ ÁHMIYETI - Gaypova, R.T.; Maxsetbaev, N.B. (ILIM hám JÁMIYET, 2025)
This article focuses on teaching "project-based" lessons in geography in general secondary schools and their significance, the opinions of foreign scholars, the role of project-based lessons in developing students' knowledge, skills, and competencies, enhancing their level of thinking, and increasing lesson effectiveness.